Effect of Bap and Coconut Water on Pamelo (Citrus maxima (Burm.) Merr.) Seed Initiation in Vitro - Zia, Khaliza; Nilahayati, Nilahayati; Nazirah, Laila; Handayani, Rd. Selvy; Hafifah, Hafifah (Journal of Tropical Horticulture, 2021)
Pomelo is a fruit commodity with high economic value and is in great demand by the public. Pomelo contains vitamins, proteins, and minerals the body needs to fulfill balanced nutrition. Aceh is one of the areas producing pomelo in Indonesia. The production of pamelo in Aceh is generally not optimal due to the limited supply of seeds that cannot be conventionally germinated. Plant tissue culture is one of the methods of propagation that can produce new plants in a relatively shorter time and large quantities. This research aims to determine the effect of natural and synthetic growth regulators on the growth of pomelo plants in vitro. The research used a factorial Randomized Block Design (RBD) of 2 factors. The first factor is the concentration of Benzyl Amino Purine (BAP) (0 mg/L, 1 mg/L, and 2 mg/L) and concentration of coconut water (0%, 15% and 30%).